Genetic engineering advances and Qur’anic exegesis perspectives and challenges: the case of human cloning - Ibrahim , Esam Eltigani Mohamed (2014)

(untitled)
Cloning via somatic cell nuclear transfer is a process by which mammals are reproduced asexually. Although human cloning is currently prohibited by most countries and denounced by the scientific community, some argue that it is within the reaches of genetic engineering and biotechnology. To date, most cloned mammals derived by nuclear transfer die during pregnancy, and those that survive the birthing process frequently face health problems. Nevertheless, it is often argued that these are technical problems that will be solved by scientific progress in the foreseeable future. But some of these problems may very well prove to be unsolvable. From an Islamic perspective, human cloning, if achieved, does not bring into question any Islamic belief, as it is merely a manipulation of God’s creation. However, it definitely offers some challenges to all the sciences of Islam, including Qur’anic exegesis. This article attempts to analyze the implications of human cloning for Qur’anic exegesis by re-visiting the meanings of some of the Qur’anic verses pertaining to issue of creation, reproduction and infertility.